Measuring successful processes of knowledge co-production for managing climate change and associated environmental stressors: Adaptation policies and practices to support Indian farmers. (15th March 2021) - Singh, Ranjay K.; Singh, Anshuman; Zander, Kerstin K.; Mathew, Supriya; Kumar, Arvind
Abstract: Poor access to external resources, and a lack of affordable technologies compatible with socio-economic and ecological settings of rural livelihoods lead to high vulnerability of subsistence farmers to climate change and associated environmental stressors. Traditional knowledge (TK) plays a pivotal role in improving the adaptive capacity of such farmers to cope with these stressors. In India, most of the policies aiming to improve farmers' adaptive capacity are based on a top-down approach and barely consider farmers' TK. Policies can be made more inclusive by mainstreaming stakeholders' perspectives, an approach termed as knowledge co-production. Our study uses a knowledge co-production framework to (i) assess the current state of emphasis on TK and knowledge co-production processes in Indian policies on agricultural adaptation to climate change and associated environmental stressors, (ii) understand the status of TK-led knowledge co-production at the practice level, and (iii) assess the successes and gaps in incorporating TK in agricultural adaptation at the policy and practice levels to manage these stressors. Based on a systematic literature review, we found that despite emphasis on integration of TK, no Indian policy was successful in terms of stakeholder participation and in covering various dimensions of knowledge co-production. Most of the policies covered either two ( knowledge gathering and application ) or three ( gathering, integration and application ) dimensions. The term TK was also not clearly defined and it was unclear how to mainstream it into the process for successful outcomes. Co-production process was adjudged to be fairly successful at the practice level in some of the sectors (e.g., management of soil and water resources) where most of the dimensions were covered and stakeholders participated in various steps of co-production. There were significant differences in the success of co-production within (e.g., crop varieties) and between (e.g., crop and natural resource management) the sectors. We found a considerable gap at policy and practice levels on success of knowledge co-production. Insights from the study could help policy-makers to improve policies for the agricultural sector to better adapt to climate change and associated environmental stressors through the recognition and integration of farmers' TK. Graphical abstract: Image 1 Highlights: Resource-poor farmers often employ traditional knowledge (TK) to adapt to environmental stresses. A co-production framework was applied to understand processes in TK-led knowledge co-production. Policy level gaps in systematically mainstreaming TK-led processes were evident. Inclusion of different dimensions showed fairly efficient of co-production process at practice level. Our co-production framework provides relevant insights to future policies on sustainable agricultural adaptation.